Company Strategy in Cultivating Disciplined Attendance Attitudes of Employees - Nur Aini, Habibah; Addin Linando, Jaya; Suhartini, Suhartini (Cita konsultindo, 2024)
Study This aims to know the factors that become company constraints and strategies for realizing the presence of attitude discipline among employees at PT. Sunindo Prima Gate. Research This uses an approach study with the technique of interview and observation data collection. Based on the results, the study found that the actor's reason for delay covering personal habits like management, bad time, low​ motivation work, and lack of awareness about the importance of discipline in operating is not quite enough to answer for a professional. In addition, the absence of awards also contributes to low motivation, the emptiness of the HRD position, and lack of supervision, which also results in violation of discipline and often not​ getting strict sanctions. Research​ This highlights the emptiness of the HRD position at PT. Sunindo Gapura Prima has a significant impact on employee discipline. The absence of an HRD who should play a role as a connector between management and employees causes a lack of systematic monitoring and evaluation​ of behavior-disciplined employees. Without the existence of HRD, the company has difficulty consistently applying policy discipline and giving further instructions​ for repairing problem discipline.